Business Strategy, Financial Distress And Environment Uncertainty On Tax Avoidance (Case Study On Asean Countries) - Rahmadhani, Fadilla; Arieftiara, Dianwicaksih (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Tax avoidance can reduce state revenue and interfere with the efficient allocation of resources. Tax avoidance is a special challenge for developing countries, especially in the ASEAN region, which has a large tax potential but has not been optimally utilized. This research is a quantitative study that aims to test empirically the effect of business strategy, financial distress and environmental uncertainty on tax avoidance proxied by using book tax different (BTD). The research population is ASEAN countries and Indonesia and Thailand as research samples during the 2018-2022 period. The analysis technique used is multiple linear regression analysis with panel data regression using the STATA program. The results of this study obtained that (1) business strategy has no significant effect on tax avoidance, (2) financial distress has a significant negative effect on tax avoidance and (3) environmental uncertainty has no significant effect on tax avoidance.